جماليات توظيف التراث الديني في رواية أنا يوسف لأيمن العتوم - إلهام سمار (My University, 2026)
Abstract: This study examines the aesthetics of employing religious heritage in the novel l am joseph by ayman al- atoum proceeding from the endeaor of novelists to evoke religious legacy for diverse artistic and intellectual purposes that serve the human experience in its moral and realistic dimensions. This literary work serves as a model in which the author inspired the koranic text and reformulated it with a creative vision that transcends literal transmission into horizons of aesthetic interpretation addressing sublime themes through a narrative style that blends historical facts with artistic imagination. The research focused on monitoring the relationship between the koranic and the novelistic texts in terms of occurrence and employment demonstrating the impact of this evocation in enriching the dramatic structure and revealing deep human insights. The study concludes that the employment of heritage was not merely a restoration of the past but rather formed an effective expressive tool that contributed to the openness of the text to multiple interpretations highlighting the novelists ability to create a delicate balance between religious reference and artistic innovation. ------------------------- الملخص: تتناول هذه الدراسة جمالية توظيف التراث الديني في رواية " أنا يوسف" لأيمن العتوم، انطلاقا من سعي الروائيين لاستحضار الموروث الديني لغايات فنية وفكرية متعددة تخدم التجربة الإنسانية في أبعادها القيمية والواقعية. حيث يعد هذا العمل الروائي نموذجا استلهم فيه الكاتب النص القرآني وأعاد صياغته برؤية إبداعية تتجاوز النقل الحرفي إلى فضاءات التأويل الجمالي، معالجا مضامين سامية بأسلوب سردي يمزج بين الوقائع التاريخية والخيال الفني. وقد ركز البحث على رصد العلاقة بين النصين القرآني والروائي من حيث التوارد والتوظيف، مبينا أثر هذا الاستحضار في إثراء البناء الدرامي والكشف عن الرؤى الإنسانية العميقة. وتخلص الدراسة إلى أن توظيف التراث لم يكن مجرد استعادة للماضي، بل شكل أداة تعبيرية فعالة ساهمت في انفتاح النص على تأويلات متعددة، وأبرزت قدرة الروائي على خلق توازن دقيق بين المرجعية الدينية والابتكار الفني. ---------------- Résumé : Ce travail étudie l’esthétique de l’utilisation du patrimoine religieux dans le roman « Moi, Youssef » d’Ayman Al-‘Atoum, à partir de la quête des romanciers pour invoquer l’héritage religieux à des fins artistiques et intellectuelles diverses servant l’expérience humaine dans ses dimensions axiologiques et réalistes. Cette œuvre romanesque constitue un modèle dans lequel l’auteur s’est inspiré du texte coranique et l’a reformulé avec une vision créative dépassant la simple reproduction littérale pour atteindre des espaces d’interprétation esthétique, traitant des contenus élevés par un style narratif mêlant faits historiques et imaginaire artistique. La recherche s’est concentrée sur l’observation de la relation entre les deux textes — le coranique et le romanesque — en termes de convergence et d’utilisation, montrant l’effet de cette évocation dans l’enrichissement de la construction dramatique et la révélation de profondes visions humaines. L’étude conclut que l’emploi du patrimoine n’a pas été une simple restitution du passé, mais a constitué un outil expressif efficace ayant contribué à l’ouverture du texte à de multiples interprétations, et a mis en lumière la capacité du romancier à créer un équilibre subtil entre la référence religieuse et l’innovation artistique.
Keywords: Heritage; religion; joseph; novel; aesthetic.; التراث، الدين، يوسف، رواية، جمالية; patrimoine; Youssef; roman; esthétique